Alkali environments in tellurite glasses - Barney, Emma R.; Hannon, Alex C.; Holland, Diane; Umesaki, Norimasa; Tatsumisago, Masahiro (Elsevier, 2015)
Neutron diffraction measurements are reported for five binary alkali tellurite glasses, xM2O · (100 − x)TeO2 (containing 10 and 20 mol% K2O, 10 and 19 mol% Na2O, and 20 mol% 7Li2O), together with 23Na MAS NMR measurements for the sodium containing glasses. Differences between neutron correlation functions are used to extract information about the local environments of lithium and sodium. The Na–O bond length is 2.37(1) Å and the average Na–O coordination number, nNaO, decreases from 5.2(2) for x = 10 mol% Na2O to 4.6(1) for x = 19 mol% Na2O. The average Li–O coordination number, nLiO, is 3.9(1) for the glass with x = 20 mol% Li2O and the Li–O bond length is 2.078(2) Å. As x increases from 10 to 19 mol% Na2O, the 23Na MAS NMR peak moves downfield, confirming an earlier report of a correlation of peak position with sodium coordination number. The close agreement of the maximum in the Te–O bond distribution for sodium and potassium tellurite glasses of the same composition, coupled with the extraction of reasonable alkali coordination numbers using isostoichiometric differences, gives strong evidence that the tellurium environment in alkali tellurites is independent of the size of the modifier cation used.